Trend Knowledge Sharing pada Learning Management System untuk menghadapi Tantangan - Wicaksana, Surya Permadi; Durunavis, Dede Adika; Widayanti, Wiwit (Reputasi: Jurnal Rekayasa Perangkat Lunak, 2024)
A web-based tool called Learning Management System (LMS) is used in distance learning to organize, conduct, and evaluate educational processes. Knowledge sharing is a vital aspect of LMS Usage crucial to raising learning standards, promoting teamwork, and building vibrant learning communities. However, implementing knowledge sharing often needs to be addressed such as students' inadequate practice and comprehension of the subject matter. One suggestion for balancing the learning process in an LMS is mentoring. This research examines the integration of LMS with mentoring to overcome these obstacles. Through article search using Google Scholar and Publish or Perish software, 500 articles from 2020 to 2023 were analyzed. The search result data was then visualized using VOSViewer. The results show that combining LMS with mentoring can increase the effectiveness of online learning and overcome various barriers. There is a need to expand the focus of LMS implementation to include teachers to create a more comprehensive learning experience.